Potential impacts of reduced seafood consumption on myocardial infarction among coastal First Nations in British Columbia, Canada - Marushka, Lesya; Hu, Xue Feng; Kenny, Tiff-Annie; Batal, Malek; Fediuk, Karen; Sadik, Tonio; Golden, Christopher D.; Cheung, William W. L.; Salomon, Anne K.; Chan, Hing Man (FACETS, 2024)
The objective of this study is to examine the potential cardiovascular risk of climate-related declines in seafood consumption among First Nations in British Columbia by assessing the combined effects of reduced omega-3 fatty acids and mercury intake from seafood on the risk of myocardial infarction (MI) in 2050 relative to 2009. The data were derived from the First Nations Food, Nutrition, and Environment Study. Seafood consumption among 369 randomly selected participants was estimated, and hair mercury concentrations were measured. Declines in seafood consumption were modelled based on previously projected climate change scenarios, and the associated changes in nutrients and contaminants were used to estimate the cardiovascular risk. Reduced seafood consumption was projected to increase the risk of MI by 4.5%–6.5% among older individuals (≥50 years), by 1.9%–2.6% in men, and by 1.3%–1.8% in women under lower and upper climate change scenarios, respectively. Reduced seafood consumption may have profound cardiovascular implications. Effective strategies are needed to promote sustainable seafood harvests and access to seafood for coastal First Nations.